The Big Society in an age of austerity: threats and opportunities for Health Consumer and Patients' Organizations in England. (6th March 2014) - Baggott, Rob; Jones, Kathryn
Abstract: Background and Objective: Health consumer and patients' organizations (HCPOs) seek to influence policy. But how are they affected by developments in the policy context and political environment? Design: The article draws on original research into HCPOs in the UK by the authors, including a major survey undertaken in 1999 and interviews with HCPOs and policymakers between 2000 and 2003 as well as a further survey in 2010. It also draws on a review of key government policies on health and the voluntary sector since 1997. Results: Developments in the political environment and policy context have created both opportunities and threats for HCPOs as they seek to influence policy. These include policies to promote choice and competition in public services; support for a greater role for the voluntary sector and civil society in health and welfare (including the current government's 'Big Society' idea); NHS reorganization; changes to the system of patient and public involvement; and austerity measures. Devolution of powers within the UK with regard to health policy and the rising profile of the EU in health matters have also had implications for HCPOs. Discussion and Conclusion: This analysis raises key issues for future research in the UK and elsewhere, such as how will HCPOs be able to maintain independence in an increasingly competitive environment? And how will they fare in an era of retrenchment? There are also challenges for HCPOs in relation to maintaining relationships in a new institutional setting characterized by multilevel governance.